Regulation of “Bilik Asmara” in Indonesian Correctional Institutions Between Human Rights and Security - Syam, Elvi Susanti; Hartawati, Andi; Purwanda, Sunardi (Ipso Jure, 2025)
The arrangement of conjugal visits or "romance rooms" for inmates in Indonesia is in a state of legal vacuum, leaving its implementation to the discretion of non-standardized correctional officers. This normative legal research aims to analyze these problems from the perspective of human rights (HAM) and state administrative law, as well as formulate proposed policy reformulation. Using legislative, comparative, and conceptual approaches, this study finds that current discretionary practices create legal uncertainty, inconsistencies, and are susceptible to abuse of authority, thus contradicting the General Principles of Good Governance (AAUPB). A comparative analysis of international jurisprudence (ECHR vs. the Italian Constitutional Court) and practice in different countries shows that although there is no absolute obligation, regulation-based conjugal visit arrangements are a global trend in support of rehabilitation goals. This study argues that the indefinite handover of authority to officers cannot be justified. As a solution, a policy reformulation model is proposed in the form of a Ministerial Regulation that comprehensively regulates principles, objective criteria, procedures, and accountability mechanisms. This regulation is recommended as a middle way to balance proportionately between the fulfillment of the right to personal life and the family of prisoners with the mitigation of security risks, in line with the mandate of Law No. 22 of 2022 concerning Corrections.